1979
DOI: 10.1080/14640747908400709
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Reaction Time and Intensity in Discrete Auditory Tasks

Abstract: The effect of signal intensity upon reaction time (RT) was studied in three auditory RT tasks in which the signal was a tone of high or low frequency. Experiment I showed the well-known negative gradient with intensity of simple RT when the subject was instructed to ignore the frequency and give the same response to both tones. But when the subject had to discriminate the frequency in a choice RT task, the RT/intensity relationship appeared to be U-shaped. Experiment II showed that when the subject was require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 14 publications
5
48
1
Order By: Relevance
“…The question of the locus of this paradoxical prolongation of RT remains open. Some evidence derived from an AFM experiment indicates that this effect is due to prolongation of sensory, rather than motor, processes (van der Molen & Keuss, 1979). However, further research is needed to settle this issue.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The question of the locus of this paradoxical prolongation of RT remains open. Some evidence derived from an AFM experiment indicates that this effect is due to prolongation of sensory, rather than motor, processes (van der Molen & Keuss, 1979). However, further research is needed to settle this issue.…”
Section: Limitationsmentioning
confidence: 99%
“…Van der Molen and Keuss (Keuss & van der Molen, 1982;van der Molen & Keuss, 1979 showed that RTs to very loud auditory stimuli were longer than those to stimuli of moderate intensity. This effect was recently demonstrated by Ja kowski and Włodarczyk (2006) for large and bright visual stimuli.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It had been reported that the louder the auditory signal is, the faster the reaction can be obtained 6 . This could provide an explanation as to why longer RTs were required for responses to the rear signal.…”
Section: Discussionmentioning
confidence: 99%